On Collaborative Governance: Building Consensus on Priorities to Manage Invasive Species Through Collective Action - Shannon Colleen Lynch (Plant-Environment Interactions)
ABSTRACT Invasive forest pests can spread across large landscapes that include numerous land‐use management jurisdictions. As such, forest pest invasions need to be addressed with collaborative efforts because a single entity is seldom able to respond to the full scope of the problem. A collaborative governance framework provides a collective decision‐making process that allows diverse sets of actors who share an interest in a policy or management issue to work together towards mutually beneficial outcomes. Here, I apply a theoretical model of collaborative governance to understand the conditions in cooperative decision‐making that led to a consensus on statewide priorities to control an important invasive pest in California, the Fusarium dieback invasive shothole borers (FD–ISHB) beetle‐pathogen invasion. This provides (1) an empirical case study of collaborative governance in action throughout the stakeholder consensus building process and (2) interrogates that case study for theoretical contributions to the literature on collaborative governance, with special focus on invasive species management. Cohesive process outcomes were born out of effective principled engagement, participants' deep understanding and dedication to the system context, and the salient forces of leadership and interdependence baked in throughout the project. Ultimately, participants devoted their time and energy to a short but intensive planning process, resulting in more capacity for joint action, trust, interdependence, and a robust action plan that was quickly implemented.